PID implementation of UMP mini automation plant part 1- heating tank - Lee, Ming Jie (2010)
A temperature control unit is a special I/O units that receive inputs directly from thermocouple, perform PID control with 2 degree of freedom and output results through open collector outputs. Temperature control is very difficult to be implemented by using ordinary control techniques, hence the purpose of this research is to describe the implementation of PID controller design based on programmable logic controller (PLC) in order to control the time to heat up a particular solution to a desired temperature. The PLC OMRON CJIM-CPU12 and the temperature control unit CJ1W-TC001 is 2 vital parts in this research. UMP mini automation plant involved in this project is initially malfunction, so reverting it back to its original functional state is set to main priority and followed by detail PID analysis of heating tank (tank 2) of UMP mini automation plant